2014
DOI: 10.1002/erv.2339
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Distribution and Validity of DSM‐IV and DSM‐5 Diagnoses of Eating Disorders in Adolescents from the Community

Abstract: Findings extend results from previous prevalence and validation studies into the adolescent age range. Improved diagnostic categories should facilitate identification of EDs and indicate targeted treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
65
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 57 publications
13
65
2
1
Order By: Relevance
“…A lower percentage, 12.8% of the total sample, 17.5% of females and 8.3% of males, met the criteria for at least one diagnosis of ED according to DSM-IV, including “ED Not Otherwise Specified”. This finding of different rates of prevalence of EDs according to criteria adopted by DSM-IV or DSM-5, is in agreement with recent data from literature highlighting, in general, an increased ability of DSM-5 criteria to identify the presence of an ED, in addition to the acknowledged ability, linked to the higher degree of inclusivity of the diagnostic criteria, to formulate a “specified ED diagnosis”, thus reducing the rate of “non – specified ED diagnosis” [34]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A lower percentage, 12.8% of the total sample, 17.5% of females and 8.3% of males, met the criteria for at least one diagnosis of ED according to DSM-IV, including “ED Not Otherwise Specified”. This finding of different rates of prevalence of EDs according to criteria adopted by DSM-IV or DSM-5, is in agreement with recent data from literature highlighting, in general, an increased ability of DSM-5 criteria to identify the presence of an ED, in addition to the acknowledged ability, linked to the higher degree of inclusivity of the diagnostic criteria, to formulate a “specified ED diagnosis”, thus reducing the rate of “non – specified ED diagnosis” [34]. …”
Section: Discussionsupporting
confidence: 91%
“…Lifetime prevalence of EDs according to DSM-IV and DSM-5 criteria were assessed by means of the Module H of the Structured Clinical Interview for DSM IV Axis I Disorder (SCID-I, Research Version, Non-Patient Edition) [33] and the Module H modified, according to DSM-5 criteria. The rationale for performing diagnosis using either DSM IV or DSM-5 criteria was related to the acknowledged increased ability of DSM-5 criteria to identify the presence of an ED and to formulate a “specified ED diagnosis”, thus reducing the rate of “non – specified ED diagnosis” [34]. …”
Section: Methodsmentioning
confidence: 99%
“…The number of EDNOS cases dropped from 2.7 to .6% for women and from .8 to .3% for men. An increase in prevalence rates of any threshold eating disorder was also found by Flament, Buchholz, et al, () who reported an increase from 1.8% (DSM‐IV) to 3.7% (DSM‐5) in a Canadian adolescent student sample. More specifically, prevalences of both AN and BED remained stable, yet BN cases increased from 1.4 to 1.6% from DSM‐IV to DSM‐5.…”
Section: Introductionsupporting
confidence: 72%
“…EDNOS/OSFED). The discrepancies outlined above contribute to complicate the interpretation of ED prevalence across studies reported in this paper, and represent a limitation of the generic psychiatric measures used, especially as EDNOS was the most frequently derived ED diagnosis during the DSM-IV era 76 and SCID was the most commonly used interview to assess ED prevalence in the current review. 62 ED specific instruments (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Recent prevalence studies based on DSM-5 criteria have already reported a decrease in prevalence rates of unspecified ED (i.e., EDNOS/OSFED), 76,116 and higher rates of AN and BN. For AN, removal of the amenorrhea criteria and broadening of the weight criteria constitutes the most important amendments, whereas the main adaptation for BN has been to reduce frequency criteria of bingeing and purging.…”
Section: Discussionmentioning
confidence: 99%